1 kHz fixed-target serial crystallography using a multilayer monochromator and an integrating pixel detector. (2019) - Tolstikova, A.; Levantino, M.; Yefanov, O.; Hennicke, V.; Fischer, P.; Meyer, J.
No abstract available